If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -2 + x + -4 = 0 Reorder the terms: -2 + -4 + 8x + x = 0 Combine like terms: -2 + -4 = -6 -6 + 8x + x = 0 Combine like terms: 8x + x = 9x -6 + 9x = 0 Solving -6 + 9x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 9x = 0 + 6 Combine like terms: -6 + 6 = 0 0 + 9x = 0 + 6 9x = 0 + 6 Combine like terms: 0 + 6 = 6 9x = 6 Divide each side by '9'. x = 0.6666666667 Simplifying x = 0.6666666667
| -2y+2x=14 | | -2x+2y=14 | | -4x=4x-4+3 | | 4x+81=-22 | | 4x+12+3=(2x-3)(2x+3) | | 4y+x=-22 | | 4x+y=-22 | | 3x^2-7x+K^2-2K=0 | | x+y=175 | | y+x=20 | | 4x(x+3)+3=(2x-3)(2x+3) | | -2.4y+0.1x=10.5 | | -2.4x+0.1y=10.5 | | 2y+3x^3-5x-y^2+3xy=8 | | 5y=-5x+10 | | 6y=6x+6 | | 6x=6y+6 | | .25(8z-4)=z+8-22 | | -2x-2(7)=-6 | | y=4(1)+2 | | 13=8+6p-7p | | 3=-4x-21 | | 2x^2-11x-124=0 | | -x(5x+-10)=50 | | -13=8-6p-7p | | 4x^4+3x^3+2x^2+x=0 | | -3z=-2 | | 0.75(x-2)=12 | | 3(2x+1)+4(x+9)=29 | | 3(x+5)=2(x-5) | | 12(x-1)=5(x-8) | | 4(x-8)=2(x+6) |